Current diagnostic modalities and clinical pitfalls in malignant secondary breast tumours - Lüdders, Dörte Wiebke; Tengg-Kobligk, Hendrik von; Hornemann, Amadeus; Thill, Marc; Franke, Folker E.; Muenstedt, Karsten; Bohlmann, Michael K. (Archives of gynecology and obstetrics, 2011)
Breast cancer is the most common malignancy in women with increasing incidence. The occurrence of metastatic disease to the breast in both females and males is relatively rare, constituting 0.5-6% of all breast malignancies. The therapy of secondary breast cancer is usually completely different from that of primary malignant lesions. Thus, early confirmation of secondary involvement is crucial to direct appropriate and to avoid potentially harmful treatment. The main focus remains to include secondary breast involvement in the differential diagnosis of breast tumours. In recent years, a number of new or improved imaging modalities have been introduced in the diagnosis of breast neoplasm. Current diagnostic concepts of metastatic neoplasm to the breast, including latest imaging modalities and their possible future applications, are presented in this review with special emphasis on possible pitfalls.
Gesehen am 15.11.2022